PENYULUHAN ALAT KONTRASEPSI DAN EFEK SAMPING SUNTIK KEPADA MASYARAKAT DI DESA AEK BAYUR KECAMATAN PADANGSIDIMPUAN BATUNADUA - Suryati Harahap; Yanna Wari Harahap (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
The family planning program is one of the most important national development programs in the context of realizing a prosperous Indonesian family. One of the main tasks of family planning (KB) development towards the development of a prosperous family is through birth control efforts that can be done by using contraception. Rapid population development will affect life in society. To prevent this problem, the government held a family planning program. The use of injectable contraception is the most popular method by the community to date. The purpose of this community service activity is so that the community can increase knowledge about injectable contraceptives as pregnancy prevention protection. Counseling is carried out using flipcharts. The population and sample of this service are couples of childbearing age as many as 15 people. This activity was carried out at the Aek Bayur Village Hall. The results of this community service were enthusiastically received by the participants as seen from the many people who asked about information on injectable contraceptives, installation procedures, contraindications, advantages and disadvantages of using this contraceptive injection. It is recommended that outreach activities in increasing knowledge about injectable contraceptives can be carried out regularly with a more frequent frequency and the range of information dissemination can also be expanded to families in general so that everyone, families and the community better know, understand about injectable contraceptives as pregnancy prevention protection.